2004
DOI: 10.1021/jf0491557
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Astringent Sensation of Soy Milk during Tofu Curd Formation

Abstract: The effect of isoflavone on soy milk and tofu astringency was investigated, and no consistency was found between an undesirable astringent taste and isoflavone contents. Isoflavone-enriched extract (approximately 39% isoflavones) showed no astringency. Soybean foods having high amounts of isoflavones showed less astringency. About 80% of isoflavones exist freely in both soy milk and tofu, but 55% of phytates (which play an important role in the formation of the tofu curd network) exist freely in the soy milk, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…1969b; Schaefer and Love 1992; Hou and Chang 2003). Phytate may also affect the taste of soymilk (Mahfuz et al. 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1969b; Schaefer and Love 1992; Hou and Chang 2003). Phytate may also affect the taste of soymilk (Mahfuz et al. 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers reported that coagulation of soymilk was affected by phytate content (Saio et al 1969b;Schaefer and Love 1992;Hou and Chang 2003). Phytate may also affect the taste of soymilk (Mahfuz et al 2004). The content of phytate in soybeans decreased gradually with storage time under 84% RH at 30C (Hou and Chang 2003) or under 65-85% RH at 20-30C (Thomas et al 1989).…”
Section: Chemical and Physical Characteristics Of Soymilkmentioning
confidence: 99%
“…The main problems facing the acceptance of these products are related to their flavor, commonly being referred to as “beany,” certain astringency and bitter taste, as well as some undesirable textural characteristics (Al Mahfuz et al . ; Chambers et al . ; Da Silva et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their lactose-free and reduced fat content, soy-based products are also a good source of protein and may provide health benefits for the consumer. The main problems facing the acceptance of these products are related to their flavor, commonly being referred to as "beany," certain astringency and bitter taste, as well as some undesirable textural characteristics (Al Mahfuz et al 2004;Chambers et al 2006;Da Silva et al 2012). In any case, the sensory problems of soy-based beverages or desserts increase with their soy protein content.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many attempts to improve the unfavorable characteristics of soybean seeds have been made [2]. It's in this context that the use of soy protein isolate (SPI) as starting material has several advantages.…”
Section: Introductionmentioning
confidence: 99%